Designers' guide to eurocode 5 : design of timber buildings : En 1995-1-1 - Porteous, Jack (ICE Publishing, 2013)
This guide interprets and assists in the use of EN 1995-1-1 structural timber. Showing typical material properties and dimensions; modifiers, and structural responses, it presents concise worked examples.
Keywords: Building, Wooden -- Standards.; Eurocodes (Standards); elektronické knihy; electronic books